Password Based Circuit Breaker Using GSM Module - B. Malleswari, K. Anitha, V. Jaikumar, A. Arun Chakravarthy (Mathematical Statistician and Engineering Applications, 2023)
An automatic electric switch known as a circuit breaker is used to safeguard an electrical circuit from harm brought on by overloading or short circuits. When we use our hands, we observe an increase in lethal electrical threats to cable workers during power line repairs because of a lack of communication and interaction between the repair employees and the power station workers. This project is made to tackle the issue with a design breaker so that only an authorised person may use it with a password in order to prevent such risks. Arduino has complete control over the system. The circuit breakers, which are switched on or off by a flashlight, are activated by entering the password into the keypad. Remote system control is possible thanks to the global mobile system (GSM) circuit. This leads to solving the problem of wasting time.